Biostratigrafija zgornjekrednih pelagičnih apnencev okolice Bovca v Julijskih Alpah - Radoičić, Rajka (Geologija, 2004)
In the western part of Julian Alps in many places small erosion remains of Late Cretaceous pelagic, light grey and reddish limestones and marls (scaglia)are preserved. These limestones and marls that contain very numerous globotruncanas overlie southwest of Bovec after a hiatus the Lower Jurassic Pliensbachian oolitic and biospariotic limestone. Between the two limestones appears an angular disconformity. Total thickness of the Upper Cretaceous limestone and marl is 8.80 m. The lower 6.20 m of the column were sampled in detail. In the scarcely 6.20 m thick section three globotruncana zones were established: Helvetotruncana helvetica (3-5 cm), Dicarinella concavata (120 cm) and Dicarinella asymetrica (490 cm). The H. helvetica zone is not developed in its entire thickness owing to the hiatus below. Deposition of theLate Cretaceous pelagic limestones started in Turonian and lasted into Campanian. The considered beds in Bovec basin are overlain by Campanian-Maastrichtian flysch beds.
Keywords: apnenec; biostratigrafija; foraminifere; fosili; Julian Alps; Julijske Alpe; kreda; Lake Kreda; paleontologija; paleontology; Slovenia; Slovenija